Dissolved Organic Matter Influences N2 Fixation in the New Caledonian Lagoon (Western Tropical South Pacific) - Benavides, Mar; Martias, Chloé; Elifantz, Hila; Berman-Frank, Ilana; Dupouy, Cécile; Bonnet, Sophie (Frontiers in Marine Science, 2018)
Specialized prokaryotes performing biological dinitrogen (N2) fixation ('diazotrophs') provide an important source of fixed nitrogen in oligotrophic marine ecosystems such as tropical and subtropical oceans. In these waters, cyanobacterial photosynthetic diazotrophs are well known to be abundant and active, yet the role and contribution of non-cyanobacterial diazotrophs are currently unclear. The latter are not photosynthetic (here called 'heterotrophic') and hence require external sources of organic matter to sustain N2 fixation. Here we added the photosynthesis inhibitor 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) to estimate the N2 fixation potential of heterotrophic diazotrophs as compared to autotrophic ones. Additionally, we explored the influence of dissolved organic matter (DOM) on these diazotrophs along a coast to open ocean gradient in the surface waters of a subtropical coral lagoon (New Caledonia). Total N2 fixation (samples not amended with DCMU) ranged from 0.66 to 1.32 nmol N L-1 d-1. The addition of DCMU reduced N2 fixation by >90%, suggesting that the contribution of heterotrophic diazotrophs to overall N2 fixation activity was minor in this environment. Higher contribution of heterotrophic diazotrophs occurred in stations closer to the shore and coincided with the decreasing lability of DOM, as shown by various colored DOM and fluorescent DOM (CDOM and FDOM) indices. This suggests that heterotrophic N2 fixation is favored when labile DOM compounds are available. We tested the response of diazotrophs (in terms of nifH gene expression and bulk N2 fixation rates) upon the addition of a mix of carbohydrates ('DOC' treatment), amino acids ('DON' treatment), and phosphonates and phosphomonesters ('DOP' treatment). While nifH expression increased significantly in Trichodesmium exposed to the DOC treatment, bulk N2 fixation rates increased significantly only in the DOP treatment. The lack of nifH expression by gammaproteobacteria, in any of the DOM addition treatments applied, questions the contribution of non-cyanobacterial diazotrophs to fixed nitrogen inputs in the New Caledonian lagoon. While the metabolism and ecology of heterotrophic diazotrophs is currently elusive, a deeper understanding of their ecology and relationship with DOM is needed in the light of increased DOM inputs in coastal zones due to anthropogenic pressure.